Travel plans: a critical comparison of the application of land use planning processes in England and Scotland - Llewellyn, Richard; Tricker, Reggie; Paton, Deborah (Transport, 2014)
A Travel Plan is a travel demand management tool which has the potential to alter the means of travel to or from any destination or origin of movement to modes of transport other than the private car. A Travel Plan typically comprises of a package of measures which interact to achieve such modal shift. Travel Plans or their equivalents have been used successfully in various parts of the world to manage travel demand. Ultimately however, the success or failure of a Travel Plan meeting its intended objectives hinges on an appropriate mechanism, usually legal, to ensure that the measures within the plan are observed and properly implemented.Although both are constituent parts of the UK, England and Scotland operate under separate legal and governance systems. In the international context of Travel Planning, this results in the unique and novel situation of two countries of virtually identical demographics but with potentially different implementation systems. This paper investigates the differences between the two approaches adopted, making reference to best practice examples from local authorities in both countries.Firstly, the legal position of Travel Plans is investigated through a comparison of the relevant English and Scottish legislation. Particular reference is made to the ability of such legislation to facilitate ‘soft’ measures and secure a long term agreement with owners or occupiers. Both of these aspects are critical to the successful enforcement of Travel Plans.Evidence from previous research suggests that central government policy can be used as an incentive to ensure that local authorities promote and monitor Travel Plan activity associated with development. However, given the legal complexities of land use planning and the limited resources of local authorities, clear and direct national government guidance is also considered an important factor. In recognition of these facts, the paper goes on to compare and contrast the approaches to policy and guidance adopted by the two countries.Through a combination of desktop and interview surveys, the practical application of the legal, policy and guidance aspects of travel planning in the two countries is reviewed. Using a review of local authority approaches in England and Scotland, conclusions are drawn with regard to the relevant strengths and weaknesses of approaches adopted in each country.Previous research suggests that the implementation of single-use development Travel Plans is now widely observable across the UK, albeit with varying degrees of long-term success. However, implementation of Travel Plans across wide area, mixed use development carries with it additional challenges, both in legal and practical terms. Specific reference is made to how local authorities are able to address these issues.The paper concludes with a discussion of these findings and makes a number of suggestions on how the processes may be improved to facilitate better application, monitoring and enforcement of Travel Plans across the UK and internationally.First published online: 09 May 2014